Bridging the Gap Between Knowledge and Practices Pertaining to Naloxone Use: A Single-Institution Experience in North Carolina - Michael S. Argenyi; Gisele Bailey; Christopher J. McLouth; Erin Barnes; Candice J. McNeil (Journal of Patient-Centered Research and Reviews)
Naloxone is a life-saving medication for opioid overdose, which claims many lives annually. This study investigated provider attitudes about, beliefs about, and barriers to naloxone use to inform an increase in provider prescription of naloxone. The survey took place at a large Southern tertiary health center. An adapted REDCap survey utilizing validated questions was distributed via institutional e-mail listservs. The results (N = 181) were analyzed using descriptive and chi-square statistics. While 90.9% of the providers had heard of the strategy of prescribing naloxone to prevent overdose, only 72.1% of providers would have considered prescribing naloxone. Providers reported implementing treatment or referrals when informed about nonprescribed opioid use (49.4%), when informed about suspected opioid use disorder (50.6%), or when patients asked for opioid use treatment advice or referral (24.4%). Responses indicated that providers are aware of prescribing naloxone to prevent overdose; however, discrepancies existed between providers’ knowledge and their willingness to prescribe naloxone. Providers’ reluctance to prescribe is partially explained by unfamiliarity with the safety of naloxone and counseling practices surrounding the drug, as well as the belief that prescribing naloxone encourages continued nonprescribed use of opioids. To increase provider comfort, training programs surrounding the safety and counseling practices of naloxone should be implemented.